Graphene oxide-based NET strategy for enhanced colorimetric sensing of miRNA - Lee, Jieon; Kim, Young-kwan; Lee, Sangwoo; Yoon, Seokjoo; Kim, Woo-keun (ELSEVIER SCIENCE SA, 2019)
MicroRNAs (miRNAs), short non-coding RNAs, have emerged as promising next-generation biomarkers of diverse diseases. In general, conventional quantitative real-time PCR and miRNA microarray methods have been utilized for the quantitative detection of miRNA. However, owing to their complicated procedures and expensive reagents/instruments, these methods cannot be widely applied by medical experts such as doctors and nurses, and are thus limited for practical clinical application. Here, we established a new graphene oxide (GO)-based NET strategy for facile miRNA detection with enhanced sensitivity, which is applicable for point-of-care testing (POCT). The proposed miRNA sensing strategy is fundamentally based on the peroxidase-mimicking DNAzyme (Dz) mediated colorimetric assay in response to target miRNA using rationally designed duplex molecular beacon (dMB). The application of GO as a net in this basic system (designated GONET) allows for gathering of the target-dependently activated Dz, which enhances the sensitivity and extends the applicability for POCT. The GONET system provides clear visualization of the target at the 10(-9) M scale with the naked eye without any complicated amplification steps.
Keywords: HYBRIDIZATION CHAIN-REACTION; PEPTIDE NUCLEIC-ACID; CIRCULATING MICRORNAS; POTENTIAL BIOMARKER; GOLD NANOPARTICLES; DNA; PLATFORM; CANCER; STRAND; ASSAY